Analysis of the Effect of Pre-Retirement Withdrawals: VBA Simulation - Muhammad Rifa’ie Khalid Ibni Walid; Mazlynda Md Yusuf; Sukono (Malaysian Journal of Science Health & Technology, 2024)
Malaysia’s trajectory towards becoming an aging nation, coupled with the current healthy life expectancy (HALE) and overall life expectancy, has caused the population to face a higher risk of inadequate retirement income. Private sector workers are obligated to save through the Employees Provident Fund (EPF). However, recent pre-retirement withdrawal policies during the COVID-19 pandemic have raised concerns about future retirement income adequacy. This study simulated accumulated EPF values for SPM and Degree holders, analysed withdrawal effects, determined the income adequacy ratio using replacement rates, and identified poverty status among retirees using VBA Excel. While Degree holders demonstrated the highest savings and expected retirement income, SPM holders had higher replacement rates. Pre-retirement withdrawals had a greater impact on SPM holders due to their lower accumulated value at retirement. According to the scenarios simulated, the highest reduction is 26.76 percent for SPM and 20.85 percent for Degree. Even though none of the analysed scenarios resulted in income during retirement being lower than the poverty line income, they may have a high chance of facing insufficient income for a comfortable retirement year. Hence, policymakers should carefully monitor, control, and plan available and future pre-retirement withdrawal policies, as increased withdrawals can shift retirees’ situations from adequate to inadequate retirement income.